The Doing Business Indicators, Economic Growth and Regulatory Reform - Hanusch, Marek (World Bank, Washington, DC, 2012)
Improving the investment climate is among the top priorities in development. The World Bank Group's Doing Business reports have become an important guide and benchmark to inform regulatory reforms aimed at unleashing the potential of the private sector. This paper discusses the potential role of the Doing Business Indicators in the reform process. Generally, the Doing Business studies are constrained in their prescriptive power for policy making. However, governments that nonetheless choose to use the Doing Business reports for guidance in the reform process can aim to improve their Doing Business ranking to enhance the visibility of their general reform efforts; or they can aim at maximizing the impact of reform on economic growth. In this case, the evidence suggests that focusing on indicators relating to credit and the enforcement of contracts is the most important. Indicators related to cost have the largest potential for fostering growth.